Parabacteroides distasonis regulates the infectivity and pathogenicity of SVCV at different water temperatures - Yujun Zhang; Yan Gao; Chen Li; Yong-An Zhang; Yuanan Lu; Jing Ye; Xueqin Liu (Microbiome)
Abstract Background Spring viremia of carp virus (SVCV) infects a wide range of fish species and causes high mortality rates in aquaculture. This viral infection is characterized by seasonal outbreaks that are temperature-dependent. However, the specific mechanism behind temperature-dependent SVCV infectivity and pathogenicity remains unclear. Given the high sensitivity of the composition of intestinal microbiota to temperature changes, it would be interesting to investigate if the intestinal microbiota of fish could play a role in modulating the infectivity of SVCV at different temperatures. Results Our study found that significantly higher infectivity and pathogenicity of SVCV infection in zebrafish occurred at relatively lower temperature. Comparative analysis of the intestinal microbiota in zebrafish exposed to high- and low-temperature conditions revealed that temperature influenced the abundance and diversity of the intestinal microbiota in zebrafish. A significantly higher abundance of Parabacteroides distasonis and its metabolite secondary bile acid (deoxycholic acid, DCA) was detected in the intestine of zebrafish exposed to high temperature. Both colonization of Parabacteroides distasonis and feeding of DCA to zebrafish at low temperature significantly reduced the mortality caused by SVCV. An in vitro assay demonstrated that DCA could inhibit the assembly and release of SVCV. Notably, DCA also showed an inhibitory effect on the infectious hematopoietic necrosis virus, another Rhabdoviridae member known to be more infectious at low temperature. Conclusions This study provides evidence that temperature can be an important factor to influence the composition of intestinal microbiota in zebrafish, consequently impacting the infectivity and pathogenicity of SVCV. The findings highlight the enrichment of Parabacteroides distasonis and its derivative, DCA, in the intestines of zebrafish raised at high temperature, and they possess an important role in preventing the infection of SVCV and other Rhabdoviridae members in host fish. Video Abstract